2020
DOI: 10.1155/2020/7503605
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analyses Identify Immune-Related Signature Associated with Qingyihuaji Formula for Treatment of Pancreatic Ductal Adenocarcinoma Using Network Pharmacology and Weighted Gene Co-Expression Network

Abstract: The study aimed to clarify the potential immune-related targets and mechanisms of Qingyihuaji Formula (QYHJ) against pancreatic cancer (PC) through network pharmacology and weighted gene co-expression network analysis (WGCNA). Active ingredients of herbs in QYHJ were identified by the TCMSP database. Then, the putative targets of active ingredients were predicted with SwissTargetPrediction and the STITCH databases. The expression profiles of GSE32676 were downloaded from the GEO database. WGCNA was used to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 50 publications
3
7
0
Order By: Relevance
“…A network was established to analyze the QYHJ target genes and PDAC target genes. Through this analysis, 11 overlapped genes were identified, which is in partial agreement with our earlier research on immune-related targets of QYHJ in the context of PDAC [134][135][136]. In order to conduct further validation, a set of six key genes was chosen.…”
Section: Herbal Medicine In Vitro Assaysupporting
confidence: 71%
“…A network was established to analyze the QYHJ target genes and PDAC target genes. Through this analysis, 11 overlapped genes were identified, which is in partial agreement with our earlier research on immune-related targets of QYHJ in the context of PDAC [134][135][136]. In order to conduct further validation, a set of six key genes was chosen.…”
Section: Herbal Medicine In Vitro Assaysupporting
confidence: 71%
“…Pharmacology of networks is a cross-discipline based on systems biology and combines systems biology, polypharmacology, computational biology, network analysis, and other disciplines [ 13 ]. In addition, numerous researches have demonstrated that network pharmacology is a practical method used to predict drug targets from the perspective of studying TCM macroregulation mechanisms [ 14 ]. Hence, we investigated that the potential therapeutic targets and pathways of SCI are treated by AM&AS using network pharmacology, a molecular docking study that was conducted to further predict how AM&AS will recognize and interact with its predicted targets.…”
Section: Introductionmentioning
confidence: 99%
“…In modern research, some references reflect the importance and practicability of network pharmacology [ 39 , 40 ]. Through network pharmacology, Qian [ 41 ] found the potential immune-related targets and mechanisms of the Qingyihuaji formula against pancreatic cancer through network pharmacology and WGCNA, and Zhou [ 40 ] verified the mechanism of the injection of the compound Kushen in treating esophageal cancer, also through network pharmacology combined with WGCNA. Network pharmacology can often identify the direction of our research, thereby reducing the ambiguity of the research direction and the waste of manpower and material resources.…”
Section: Discussionmentioning
confidence: 99%